EXPRESSION OF CALRETININ IN AMELOBLASTOMA AND ODONTOGENIC CYST IN A.W. SJAHRANIE GENERAL HOSPITAL SAMARINDA - Pramasari, Cristiani Nadya; Irawiraman, Hadi; Sawitri, Endang; Muthi’ah, Nisa; Sulistiani, Dewi Arsih; Prinadira, Sarah (Dentino: Jurnal Kedokteran Gigi, 2024)
Background : Ameloblastoma and odontogenic cysts have similar clinical and radiographic features but different treatments. Diagnosis is established by histologic features, but sometimes this step have difficulty making appropriate assessment because epithelial cells can show various variations. Preoperative misdiagnosis may result in inefficient treatment. In such situations, immunohistochemistry (IHC) with the use of proper markers might be needed for the differentiation of these lesions. Purpose : This study aimed to assess calretinin expression in ameloblastoma and various odontogenic cysts so that calretinin can be used as a specific diagnostic marker for ameloblastoma. Method : This was a retrospective analytical study of immunohistochemical examination of calretinin expression in ameloblastoma and odontogenic cysts. A total of eighty cases, in which thirty four cases of ameloblastoma and forty six cases of odontogenic cysts were included in the study. Slides were made from the paraffin blocks of each case and were stained immunohistochemically with calretinin. Results : In ameloblastoma, almost all subjects expressed calretinin, i.e. 33 (97.1%), followed by radicular cyst 7 (46.7%), odontogenic cyst 2 (40.0%), then dentigerous cyst 6 (26.1%) and OKC 0 (0.0%). The results of the analysis of the Chi-Square test showed a significant difference with a p-value < 0.001. Conclusion : The study concluded that calretinin was mainly expressed in ameloblastoma, whereas majority of  odontogenic cyst groups showed negative for calretinin in various percentages. Calretinin may be a specific immunohistochemical marker for ameloblastoma. Keywords : Ameloblastoma, Calretinin, Immunohistochemical, Odontogenic cyst, Odontogenic tumor